The energy and cost calculation for a Marx pulse generator based on input dc voltage, capacitor values and number of stages - Toudeshki, Arash Mohammadi; Mariun, Norman; Hizam, Hashim; Abdul Wahab, Noor Izzri (IEEE, 2012)
Visualization of the energy equation can simplify understanding the performance of a Marx pulse generator. In this paper, the energy of a Marx pulse generator is calculated and visualized for input dc voltage from 1 to 20 kV, value of the capacitor from 1 to 33 nF and the number of stages from 1 to 20 stages. Moreover, in order to calculate the approximate cost of the Marx pulse generator, an equation proposed and evaluated.